2001
DOI: 10.1046/j.1365-2958.2001.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a molecular switch: universal bacterial GTPases regulate ribosome function

Abstract: The GTPases comprise a protein superfamily of highly conserved molecular switches adapted to many diverse functions. These proteins are found in all domains of life and often perform essential roles in fundamental cellular processes. Analysis of data from genome sequencing projects demonstrates that bacteria possess a core of 11 universally conserved GTPases (elongation factor G and Tu, initiation factor 2, LepA, Era, Obg, ThdF/TrmE, Ffh, FtsY, EngA and YchF). Investigations aimed at understanding the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
152
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(156 citation statements)
references
References 79 publications
4
152
0
Order By: Relevance
“…Various phenotypic changes are observed in cells depleted of Obg or Era. However, numerous results suggest that the primary function of Obg/Era GTP-binding proteins is related to ribosome biogenesis or translation process, consistent with their evolutionary relationships with translation factors (16). Obg and Era are the most extensively characterized bacterial small GTP-binding proteins belonging to this family.…”
mentioning
confidence: 89%
“…Various phenotypic changes are observed in cells depleted of Obg or Era. However, numerous results suggest that the primary function of Obg/Era GTP-binding proteins is related to ribosome biogenesis or translation process, consistent with their evolutionary relationships with translation factors (16). Obg and Era are the most extensively characterized bacterial small GTP-binding proteins belonging to this family.…”
mentioning
confidence: 89%
“…Strikingly, most of these GTPases are universally conserved and can be assigned to four main ancestral groups: elongation factors (EF-G, EF-Tu, and IF2), protein secretion factors (FtsY and Ffh), Era-related GTPases (Era, EngA, and ThdF/TrmE), and Obg-re-lated proteins (Obg and YchF) (5,6). Mutational analyses in many organisms have shown that most of these GTPases are essential (7,10).…”
mentioning
confidence: 99%
“…The to as the phosphate binding or P-loop, or alternatively, the G 1 motif of bacterial GTPases (13) …”
mentioning
confidence: 99%